PENGARUH DESAIN KURIKULUM DAN KEGIATAN EKSTRAKURIKULER TERHADAP MINDSET KEWIRAUSAHAAN PESERTA DIDIK MELALUI PERAN INSPIRASI - Antika Indri Sabekti; Harini Harini; Muhammad Sabandi (STKIP Persada Khatulistiwa Sintang, 2023)
Entrepreneurship is a major factor in the economic development process that can overcome the problem of unemployment. An entrepreneurial mindset must be instilled to increase the number of participants becoming entrepreneurs who ultimately expand employment opportunities. The main driver in developing an entrepreneurial mindset is the existence of entrepreneurship education based on Bandura's social cognitive theory. The purpose of the study was to determine the effect of curriculum design and extracurricular activities on entrepreneurial mindset through the role of inspiration at SMK Negeri 1 Wonogiri. The research method used is descriptive quantitative with survey type. The population of this study were all XII grade students of SMK Negeri 1 Wonogiri. The sample respondents were 161 students with sampling techniques using simple random sampling techniques. Data were collected using questionnaire techniques and analyzed using hierarchical regression analysis with SPSS version 25.0. Based on the test results, the curriculum design variables directly have an inconsistent positive or negative and insignificant effect on the entrepreneurial mindset, while the extracurricular activities and entrepreneurial inspiration variables directly have a consistent positive and significant effect on the entrepreneurial mindset